Effects of Cognitive and Motor Dual‐Task Conditions on Reaction Time, Proprioception, and Proprioceptive Force Sense in Individuals After Anterior Cruciate Ligament Reconstruction: A Pilot Study. - Akbaşlı, Oğuzhan; Demirdel, Ertuğrul (Physiotherapy Research International, 2026)
Background and Purpose: Sensorimotor impairments are common following anterior cruciate ligament reconstruction (ACLR); however, the effects of cognitive and motor dual‐task conditions on reaction time, joint position sense, and proprioceptive force sense in the early postoperative period remain unclear. The purpose of this study was to examine the effects of single‐task, cognitive dual‐task, and motor dual‐task conditions on these sensorimotor parameters at the eighth postoperative week following ACLR. Methods: This prospective observational pilot study was conducted in individuals following ACLR. Twenty‐one participants who underwent unilateral ACLR using a hamstring autograft were included. After completion of an 8‐week home‐based rehabilitation program, assessments were performed under single‐task, cognitive dual‐task, and motor dual‐task conditions. Reaction time was evaluated using a light‐based response system, joint position sense was assessed with a passive joint repositioning task, and proprioceptive force sense was measured using a pressure biofeedback unit. Differences between task conditions were analyzed using one‐way repeated‐measures analysis of variance, with effect sizes reported as partial eta squared (ηp2). Results: Significant differences were observed among task conditions for reaction time outcomes (p < 0.001), with the best performance under single‐task conditions and the poorest performance under motor dual‐task conditions (ηp2 = 0.69–0.71). Proprioceptive force sense also differed significantly between conditions (p = 0.008, ηp2 = 0.21), with higher error values observed during the motor dual‐task condition. No significant differences were found between task conditions for joint position sense (p > 0.05). Discussion: In the early period following ACLR, increasing task demands negatively affect reaction time and proprioceptive force sense, whereas passive joint position sense appears relatively resistant to short‐term dual‐task interference. These findings suggest the relevance of incorporating dual‐task considerations into sensorimotor assessment and rehabilitation following ACLR. Trial Registration: ClinicalTrials.gov: NCT06755398